Bridge maintenance, safety, management, life-cycle sustainability and innovations proceedings of the Tenth International Conference on Bridge Maintenance, Safety and Management (IABMAS 2020), June 28-July 2, 2020, Sapporo, Japan - International Conference on Bridge Maintenance, Safety and Management 2020 : Sapporo-shi, Japan); Yokota, Hiroshi, 1955-; Frangopol, Dan M. (Boca Raton : CRC Press, 2020)
Bridge Maintenance, Safety, Management, Life-Cycle Sustainability and Innovations contains lectures and papers presented at the Tenth International Conference on Bridge Maintenance, Safety and Management (IABMAS 2020), held in Sapporo, Hokkaido, Japan, April 11-15, 2021. This volume consists of a book of extended abstracts and a multimedia device containing the full papers of 571 contributions presented at IABMAS 2020, including the T.Y. Lin Lecture, 9 Keynote Lectures, and 561 technical papers from 40 countries. The contributions presented at IABMAS 2020 deal with the state of the art as well as emerging concepts and innovative applications related to the main aspects of maintenance, safety, management, life-cycle sustainability and technological innovations of bridges. Major topics include: advanced bridge design, construction and maintenance approaches, safety, reliability and risk evaluation, life-cycle management, life-cycle sustainability, standardization, analytical models, bridge management systems, service life prediction, maintenance and management strategies, structural health monitoring, non-destructive testing and field testing, safety, resilience, robustness and redundancy, durability enhancement, repair and rehabilitation, fatigue and corrosion, extreme loads, and application of information and computer technology and artificial intelligence for bridges, among others. This volume provides both an up-to-date overview of the field of bridge engineering and significant contributions to the process of making more rational decisions on maintenance, safety, management, life-cycle sustainability and technological innovations of bridges for the purpose of enhancing the welfare of society. The Editors hope that these Proceedings will serve as a valuable reference to all concerned with bridge structure and infrastructure systems, including engineers, researchers, academics and students from all areas of bridge engineering.
OCLC-licensed vendor bibliographic record.
Keywords: Bridges -- Maintenance and repair -- Congresses; TECHNOLOGY / Construction / General; TECHNOLOGY / Engineering / Civil